Polydopamine coated hypodermic needles as a microextraction device for the determination of tricyclic antidepressants in oral fluid by direct infusion MS/MS. Issue 37 (28th June 2021) - Vejar-Vivar, Carmina; García-Valverde, María Teresa; Mardones, Claudia; Lucena, Rafael; Cárdenas, Soledad
Abstract : Hypodermic needles coated with polydopamine for the extraction of antidepressants. Abstract : In-needle microextraction consists of the confinement of the sorbent, by coating or packing, inside a metallic needle. The size of the needles reduces the eluent requirements providing an efficient preconcentration of the analytes. In this work, hypodermic needles coated with polydopamine (PDA) are presented as microextraction devices to isolate six tricyclic antidepressants from oral fluid samples. The coating consists of the in-surface polymerization of dopamine at pH 8.5 and mild conditions (room temperature and water as solvent). The PDA coating over the stainless-steel surface confers the needles with a high extraction ability towards the target analytes. After the extraction, the eluates were analyzed by direct infusion MS spectrometry, working in multiple reaction monitoring (MRM) mode, which provided a sample throughput of 30 samples per hour. The variables affecting the synthesis (number of coating cycles, the concentration of dopamine, and needle surface pre-treatment) and the extraction (sample salinity, sample loading cycles, and the number of elution strokes) were studied in depth. Under the optimum conditions, a matrix-matched calibration model was built. The limits of quantification are between 2 and 5 ng mL −1 with linear ranges up to 1000 ng mL −1 for all analytes. The precision, expressed as relative standard deviation (RSD), is better than 10% for all analytes. Accuracy was calculated as recovery, and the obtained values are between 84% and 107%. A single-blind assay was also performed to evaluate the suitability of the method for real application.